Rethinking the Existentialist Crisis of Interest in School Science through Culturally Responsive African Curriculum of STEM Science - Semali, Ladislaus M. (Advances in Social Sciences Research Journal, 2017)
Many secondary teacher educators are challenged by failure to rekindle interest in science content with future teachers who often express a lifetime of negative associations with school science. This study involved science teachers in a participatory action research project to investigate the fear of STEM science as a field of study for African students. One way to enhance interest is through informal science experiences immersed in teaching through integration (e.g., of mobile technologies or immersing students in the natural environment). Findings of the study revealed that science education is desperately in need of reform. Teachers observed that science subjects continue to be taught using traditional means of chalk and talk. They noted that failure to resolve this crisis is likely to contribute to learners disenchantment with school science, drop-out from school or likely engender students bearing long-term disinterest in formal science education.This fear originated from a long-standing myth that science is a hard subject, a misconception that must be overcome by any means necessary.